Exercise training influence on cognitive capacity and mental health within chronic obstructive pulmonary disease – A pilot study - Cheng-Siao Hong; Yu-Chih Shen; En-Ting Chang; Hui-Chuan Hou; Yi-Jen Chen (Tzu Chi Medical Journal)
Objective: Although pulmonary rehabilitation and regular exercise have improved negative emotions and cognitive capacity within cases of chronic obstructive pulmonary disease (COPD), influence by exercise training upon different cognitive and memory functions in COPD is still controversial. This investigation aimed to assess whether cognitive performance and mental health are affected by the benefits of exercise training within cases of COPD. Materials and Methods: This pilot investigation included thirty-three patients with Global Initiative for Chronic Obstructive Lung Disease stage ≥B. Based on the subjects' rights, all included patients could choose to join either the exercise group or the control group, according to their free will. Twelve patients were assigned to receive exercise treatment over a 2-month period, while the remaining 16 patients were assigned to the control group. Cognitive capacity outcomes were measured using the Wechsler Memory Scale-III Word List Test, Stroop task, and psychomotor vigilance task (PVT). Mood states were assessed through the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Results: Most cases demonstrated major improvement for BDI and BAI scorings post-60-day therapy. During PVT, the omission rate decreased, while the hit rate increased, indicating an improvement in attention performance. Furthermore, this investigation found a significant increase in immediate verbal and recognition memory for word–list test. However, no major performance shifts were found on Stroop analysis. Conclusion: This investigation demonstrated that a 2-month exercise training program resulted in significant improvement in negative emotions, immediate memory, recognition memory, and attention.